The ambiguity of leadership : a case of leadership or anti-leadership? - Alvesson, Mats, 1956- ([London] : SAGE, 2016)
This case study examines the relationship between organizational culture and leadership in a Swedish industrial company. The head of a management division, Gustaf, calls a regular quarterly meeting and the case study considers the events of these meetings in order to determine whether Gustaf adopts the style of leadership or anti-leadership.
Originally Published in: Alvesson, M. (2012). The Ambiguity of Leadership - A Case of Leadership or Anti-Leadership? In Understanding organizational culture (2nd ed., pp. 109-111). London: SAGE Publications Ltd. ISBN: 9780857025586.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Leadership -- Case studies; Corporate culture -- Case studies